Mechanical Regulation of Gene Expression in Gut Smooth Muscle Cells - Shi, Xuan-Zheng (Frontiers in Physiology, 2017)
Intraluminal contents and their movement along the gastrointestinal tract create shear stress and mechanical stretch on the gut wall. While the shear stress is important in the initiation of immediate physiological responses, the circumferential mechanical stretch, such as that in obstructive bowel disorders, exerts long-lasting impacts on bowel functions by mainly affecting the deeper muscularis externae. Recent studies demonstrate that mechanical stretch alters gene transcription in gut smooth muscle cells, and the stretch-altered gene expression (mechano-transcription) may play a critical role in pathogenesis of motility dysfunction and abdominal pain in obstruction. Specifically, stretch-induced cyclo-oxygenase-2 and other pro-inflammatory mediators in gut smooth muscle cells account for impairments of muscle contractility. Mechano-transcription of pain mediators such as nerve growth factor may contribute to visceral hypersensitivity, by sensitizing primary sensory neurons. This review aims to highlight the novel findings of mechano-transcription in the gut, and to discuss the signaling mechanisms and pathophysiological significance of mechano-transcription.